Comparative analysis of visual programming RAD tools for C++ language. - Pasikova, Tetiana; Miłosz, Elżbieta (Journal of Computer Sciences Institute, 2016)
The article presents a comparison of visual programming RAD tools for C++ language. For comparison were chosen following development environments: C ++ Builder, Visual Studio, Qt Creator. Multi-criteria comparative analysis and selection of the best learning environment visual programming in C ++ were carried out on the basis of the manufacturer and the experiment with students.